A Case of Chronic Intranasal Cocaine Abuse Masquerading and Exacerbating Underlying Orbital IgG4-Related Disease. Issue 1 (13th July 2022) - Bruce, Carleigh N.; Clark, Thomas J. E.; Ratiani, Mariam; Stahulak, Andrea; Griepentrog, Gregory J.
Abstract : Chronic cocaine use may lead to widespread intranasal inflammation and necrosis. Cases of cocaine use affecting the orbit have been reported in the literature with a clinical spectrum ranging from inflammation-induced p-anti-cytoplasmic neutrophil autoantibodies positive vasculitis to severe midline destructive lesions resulting in orbital apex syndrome. Here, we present a case of chronic intranasal cocaine abuse with midline destruction that initially obscured diagnosis of, and is hypothesized to have exacerbated, underlying IgG4-Related Disease (IgG4-RD) of the orbit over a 2-year period. Abstract : The authors present a case of severe chronic intranasal cocaine abuse that obscured the diagnosis of, and likely exacerbated, concomitant IgG4-related disease of the orbit.